2013
DOI: 10.4236/ajps.2013.48195
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Use of Herbicide and Crop Mulch in Suppressing Weed Growth in a Dry-Seeded Rice System

Abstract: Dry-seeded rice production systems are increasing in many Asian countries because of labor and water scarcities. However, weeds are the main biological constraints in these systems. Herbicides are widely used to manage weeds but they do not provide effective weed control. The use of crop residue as mulch can suppress weed emergence and weed biomass but mulch alone does not provide effective weed control. The integrated use of herbicide and mulch, however, could provide more effective and sustainable weed contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
(34 reference statements)
3
6
0
Order By: Relevance
“… 28 Similarly, it was reported that the combined use of herbicide and mulch provided more effective and sustainable weed control in dry-seeded rice systems. 19 Our results are in agreement with the findings that a combination of herbicide and mulch suppresses weed growth more effectively than the mulch with no herbicide.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“… 28 Similarly, it was reported that the combined use of herbicide and mulch provided more effective and sustainable weed control in dry-seeded rice systems. 19 Our results are in agreement with the findings that a combination of herbicide and mulch suppresses weed growth more effectively than the mulch with no herbicide.…”
Section: Resultssupporting
confidence: 92%
“…For example, an integrated use of mulch and herbicide provided more effective and sustainable weed control which subsequently increased crop yield in the seeded rice systems. 19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These previous researches showed mixed results, from no interaction (Chauhan & Abugho 2013b;Mathers & Case 2010), antagonism (Chauhan & Abugho 2012;Teasdale et al 2003) or synergism (Mathers & Case 2010;Teasdale et al 2005) depending on the type and rate of herbicides and crop residues used. For instance, Chauhan and Abugho (2013b) reported that application of oxadiazon at 0.5 kg a.i. ha -1 , followed by fenoxaprop plus ethoxysulfuron at 0.45 kg a.i.…”
Section: Phyllanthus Amarus Total -----------------------------------mentioning
confidence: 98%
“…In the existing application of PHB-supported pesticide films, the research on the mechanical and optical properties of the films is rarely reported. Other biodegradable materials that integrated herbicides with mulching film for sustained and effective weed control have been reported [ 16 , 17 ]. In the application of biodegradable plastic mulching film for controlling soil-borne disease, Liang et al prepared biodegradable water-triggered chitosan/hydroxypropylmethyl cellulose metalaxyl mulch film for sustained control of Phytophthora sojae in soybean [ 18 ].…”
Section: Introductionmentioning
confidence: 99%